Hank Aaron Civil Rights Crusader Through the Game of Baseball - Zweck, Dustin (My University, 2011)
In this paper, this author will make important connections between civil rights and baseball in United States history. If one were to connect civil rights and baseball it would take much more time and effort than what this author had to give. This paper is about Henry Aaron and Civil Rights in the United States, specifically Milwaukee, Wisconsin. Through the access of two great online newspaper databases and many great secondary sources this paper will give new dynamic insight about Henry Aaron and the city of Milwaukee.
Keywords: Aaron, Hank, 1934-; African American baseball players--Wisconsin--Milwaukee; Civil rights--Wisconsin--Milwaukee; Civil rights--United States--History; Milwaukee (Wis.)--Race relations